Validation of five diatom novelties published in “Freshwater Benthic Diatoms of Central Europe” and taxonomic treatment of the neglected species Tryblionella hantzschiana - Kusber, Wolf-Henning; Cantonati, Marco; Lange-Bertalot, Horst (Phytotaxa, 2017)
In July 2017, Lange-Bertalot et al. (2017) published a revised and translated version of Hofmann et al. (2013)’s book on freshwater benthic diatoms of Central Europe. The revised edition includes a few nomenclatural novelties which neither conform to the Melbourne Code (McNeill et al. 2012) nor to the upcoming Shenzhen Code (see Turland et al. 2017). The treatment of Tryblionella gracilis W.Sm. and T. hantzschiana Grunow shows how nomenclatural and taxonomic data can sometimes be confusing. This paper validates five names invalidly published in Lange-Bertalot et al. (2017) whilst the valid but previously neglected name T. hantzschiana is proposed to replace Tryblionella tryblio Cantonati et Lange-Bert., nom. inval. The registration numbers refer to PhycoBank (Kusber et al. 2017) a registration system on algae (Barkworth et al. 2016) which recently went online.